Soluble c-erbB-2 fragment in serum correlates with disease stage and predicts for shortened survival in patients with early stage and advanced breast cancer. - Kandl, H. (My University, 1994)
Breast cancer is a major health problem, afflicting up to 1 in 9 women in developed countries with Western diet and life style. While screening programs have led to earlier diagnosis, including diagnosis at a pre-invasive stage in a number of women, the majority of patients with breast cancer still present with clinically detectable, invasive breast cancer, which even if clinically localised still carries the risk of systemic micrometastases, Such patients have been shown to benefit both in terms of disease free as well as of overall survival from the addition of adjuvant systemic treatment. The identification of progostic factors which can be used to tailor specific forms of adjuvant treatment to the patient's disease has been an important goal of breast cancer research during the last 20 years. A particularly important goal is the early identification of poor risk patients, who may benefit from aggressive intervention with intensive chemotherapy, While many prognostic markers, including nodal status, hormone-receptor-status, ploidy and growth fraction and the expression of various oncogenes and proto-oncogenes by the tumor cells have been proposed as prognostic factors, the results, to date, have been equivocal for a number of these. Recently there has been much. interest in the prognostic importance of cerbB- 2 protein in breast cancer. Most of these studies have concentrated on immunohistochemically stainable e-erb-2 in tumor tissue. This dissertation focusses on the prognostic impact of the soluble c-erbB-2 protein in the serum of breast cancer patients treated at the Breast Clinic of tne Johannesburg Hospital and University of the Witwatersrand. The results of this investigation have been reported under the title "Soluble c-erhB-2 fragment in Serum Correlates With Disease Stage and Predicts for Shortened Survival in Patients with Early Stage and Advanced Breast Cancer" by H. Kandt, L. Seymour & W.R. Bezwoda, Published in British Journal of Cancer, Vo170 p739-742" 1994.
A research report submitted to the Faculty of Medicine university of tho Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of science in Medicine.
Keywords: Breast Neoplasms diagnosis.